2005
DOI: 10.5380/ret.v4i2.5405
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Air Distribution Patterns in Surgery Rooms Under Infection Control Focus

Abstract: The problem of airborne contamination in surgical infections still raises discussion. The success of the aseptic methods and the use of medicines for the combat of infections are making most surgeons contempt the danger of the aerial particles course. A detailed knowledge of the characteristics of the contamination sources and of the ventilation system performance used at surgery rooms is necessary to guarantee that the ventilation system supplies the pollutant control in ventilation rates that assure the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The contaminants in an operating room include dust particles, textile fibers, skin scales, respiratory aerosols, and anesthesia gases. Pereira and Tribess (2004) and Chen et al (1992) reviewed the airflow patterns in operating rooms and noted the significant role of the airborne particles in the SSIs. It was indicated that there is a need to prepare optimized design criteria using the design and the performance data of an HVAC system as a future work.…”
Section: Introductionmentioning
confidence: 99%
“…The contaminants in an operating room include dust particles, textile fibers, skin scales, respiratory aerosols, and anesthesia gases. Pereira and Tribess (2004) and Chen et al (1992) reviewed the airflow patterns in operating rooms and noted the significant role of the airborne particles in the SSIs. It was indicated that there is a need to prepare optimized design criteria using the design and the performance data of an HVAC system as a future work.…”
Section: Introductionmentioning
confidence: 99%